1989
DOI: 10.1063/1.100961
|View full text |Cite
|
Sign up to set email alerts
|

Unpinned gallium oxide/GaAs interface by hydrogen and nitrogen surface plasma treatment

Abstract: The Fermi level at the Ga oxide/GaAs interface has been unpinned by rf plasma cleaning the GaAs surface in H2 and N2. Following plasma cleaning, a Ga oxide film is reactively electron beam deposited onto the substrate. Metal-oxide-semiconductor (MOS) capacitors fabricated on these structures show good high-frequency capacitance-voltage characteristics. This indicates that the density of interface states has been reduced to ∼1011 eV−1 cm−2. The MOS capacitors are found to be stable in air after several months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…To reduce the large trap densities at interfaces between In 0.53 Ga 0.47 As and the gate dielectric (typically Al 2 O 3 or HfO 2 ), various surface preparation and passivation methods are currently being investigated. [1][2][3][4][5][6][7][8][9] Interface trap densities (D it ), at least around midgap, are relatively straight-forward to detect for In 0.53 Ga 0.47 As, because of its narrow band gap (0.75 eV (Ref. 10)); they cause, for example, a frequency-dependent hump in the depletion region of capacitance-voltage (CV) characteristics, 11,12 and peaks in normalized conductance maps.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the large trap densities at interfaces between In 0.53 Ga 0.47 As and the gate dielectric (typically Al 2 O 3 or HfO 2 ), various surface preparation and passivation methods are currently being investigated. [1][2][3][4][5][6][7][8][9] Interface trap densities (D it ), at least around midgap, are relatively straight-forward to detect for In 0.53 Ga 0.47 As, because of its narrow band gap (0.75 eV (Ref. 10)); they cause, for example, a frequency-dependent hump in the depletion region of capacitance-voltage (CV) characteristics, 11,12 and peaks in normalized conductance maps.…”
Section: Introductionmentioning
confidence: 99%
“…The most suitable structure for applications is the monoclinic β-Ga 2 O 3 phase (a = 1.221 nm, b = 0.304 nm, c = 0.580 nm and β = 103.8°, space group: C2/m) which appears to be extremely stable chemically and thermally (melting point at 1800 °C) and may be an alternative choice to other transparent conductive oxide (TCO) materials (sulphide-based phosphors) usually dedicated to optoelectronic devices. Various growth techniques have been used to prepare thin films of this material: electron beam evaporation [8], spray pyrolysis deposition [9], sol gel process [7] and radiofrequency (RF) magnetron sputtering [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite having been studied in great detail for more than 35 years, this interface and the identification of the bonding configurations that cause the defects has remained challenging. [1][2][3][4] Problems with metaloxide-semiconductor ͑MOS͒ devices on GaAs and InGaAs, including frequency dispersion of capacitance and suboptimal electron mobility, have been attributed to a number of different surface species including Ga-O bonds, As-O bonds, elemental As, and As and Ga antisites. 5 Recent studies have shown that Ga-O ͑Ref.…”
mentioning
confidence: 99%
“…Possible identities for this oxidation state ͑which was not studied here͒ include Ga͑AsO 3 ͒ 3 ͑Ref. 12͒ as well as Ga͑OH͒ 3 . This state is removed easily with chemical treatment.…”
mentioning
confidence: 99%